Reinterpreting the Geneva Conventions: The Bush Administration and the Legal Framework on Torture
The rules and regulations established in the Geneva Conventions serve, in theory, to protect basic human rights during times of war, and are used to punish those found in violation. The Conventions regulate "the conduct of armed conflict and seek to limit its effects" while "specifically protect(ing